EFEKTIFITAS PROGRAM APLIKASIPhET SIMULATIONS DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI LISTRIK DINAMIS DI KELAS IX.1 SMPN 2 LINGSAR - Adin, Adin (IKIP Mataram, 2015)
Based on the observations and interviews of some physics teachers, it was found that the teacher felt that he had tried to improve the learning techniques in the classroom. But the activity and achievement of student learning not yet according to expected result. The learning pattern applied is teacher-center learning. Therefore, this is very inconsistent with the characteristics of science learning. PhET (Physics Education Technology) application program is one of the learning tools that requires students to take an active role during the learning process. This study is a classroom action research conducted in two cycles to determine the effectiveness of learning. Each cycle takes place in two sessions. Each cycle consists of the stages of planning, implementation of action, observation, evaluation, and reflection. The subject of the research is the students of class IX.1 SMPN 2 Lingsar. The results of the evaluation of cycles I and II showed a significant increase. The average score of student learning activity increased from 7.95 to 11.39 (medium to high category) and the average student evaluation score increased from 62.5 to 76.65. We concluded that the PhET application program is effective for increasing activity and student learning outcomes.